Set: pp::colors Set: pp::unicode Assumed: N Assumed: h Proved: CongrH Set: lean::pp::implicit Variable h : N → N → N Theorem CongrH {a1 a2 b1 b2 : N} (H1 : @eq N a1 b1) (H2 : @eq N a2 b2) : @eq N (h a1 a2) (h b1 b2) := @Congr N (λ x : N, N) (h a1) (h b1) a2 b2 (@Congr N (λ x : N, N → N) h h a1 b1 (@Refl (N → N → N) h) H1) H2 Set: lean::pp::implicit Variable h : N → N → N Theorem CongrH {a1 a2 b1 b2 : N} (H1 : a1 = b1) (H2 : a2 = b2) : h a1 a2 = h b1 b2 := Congr (Congr (Refl h) H1) H2 Proved: Example1 Set: lean::pp::implicit Theorem Example1 (a b c d : N) (H : @eq N a b ∧ @eq N b c ∨ @eq N a d ∧ @eq N d c) : @eq N (h a b) (h c b) := @DisjCases (@eq N a b ∧ @eq N b c) (@eq N a d ∧ @eq N d c) (h a b == h c b) H (λ H1 : @eq N a b ∧ @eq N b c, @CongrH a b c b (@Trans N a b c (@Conjunct1 (@eq N a b) (@eq N b c) H1) (@Conjunct2 (@eq N a b) (@eq N b c) H1)) (@Refl N b)) (λ H1 : @eq N a d ∧ @eq N d c, @CongrH a b c b (@Trans N a d c (@Conjunct1 (@eq N a d) (@eq N d c) H1) (@Conjunct2 (@eq N a d) (@eq N d c) H1)) (@Refl N b)) Proved: Example2 Set: lean::pp::implicit Theorem Example2 (a b c d : N) (H : @eq N a b ∧ @eq N b c ∨ @eq N a d ∧ @eq N d c) : @eq N (h a b) (h c b) := @DisjCases (@eq N a b ∧ @eq N b c) (@eq N a d ∧ @eq N d c) (@eq N (h a b) (h c b)) H (λ H1 : @eq N a b ∧ @eq N b c, @CongrH a b c b (@Trans N a b c (@Conjunct1 (a == b) (@eq N b c) H1) (@Conjunct2 (@eq N a b) (b == c) H1)) (@Refl N b)) (λ H1 : @eq N a d ∧ @eq N d c, @CongrH a b c b (@Trans N a d c (@Conjunct1 (a == d) (@eq N d c) H1) (@Conjunct2 (@eq N a d) (d == c) H1)) (@Refl N b)) Proved: Example3 Set: lean::pp::implicit Theorem Example3 (a b c d e : N) (H : a = b ∧ b = e ∧ b = c ∨ a = d ∧ d = c) : h a b = h c b := DisjCases H (λ H1 : a = b ∧ b = e ∧ b = c, CongrH (Trans (Conjunct1 H1) (Conjunct2 (Conjunct2 H1))) (Refl b)) (λ H1 : a = d ∧ d = c, CongrH (Trans (Conjunct1 H1) (Conjunct2 H1)) (Refl b)) Proved: Example4 Set: lean::pp::implicit Theorem Example4 (a b c d e : N) (H : a = b ∧ b = e ∧ b = c ∨ a = d ∧ d = c) : h a c = h c a := DisjCases H (λ H1 : a = b ∧ b = e ∧ b = c, let AeqC := Trans (Conjunct1 H1) (Conjunct2 (Conjunct2 H1)) in CongrH AeqC (Symm AeqC)) (λ H1 : a = d ∧ d = c, let AeqC := Trans (Conjunct1 H1) (Conjunct2 H1) in CongrH AeqC (Symm AeqC))